Podocyte, tubular epithelial-immune cell interplay in the pathogenesis of lupus nephritis - Chen, Jingyi; Chen, Zixiang; Mou, Xiao; Rui, Ke; Tian, Jie (Frontiers in Immunology, 2025)
Lupus nephritis (LN), a severe complication of systemic lupus erythematosus (SLE), is associated with increased morbidity and mortality. The pathogenesis of LN involves complex immune-mediated mechanisms that alter the biology of renal resident epithelial cells. Emerging evidence highlights the bidirectional interactions between immune cells and renal epithelial cells—including podocytes and tubular epithelial cells(TECs)—as critical contributors to disease progression. These interactions shape local immune responses, drive inflammatory injury, and disrupt renal function. However, the molecular and cellular basis of this crosstalk remains incompletely understood. Recent advances have uncovered key mechanisms underlying these interactions and identified potential therapeutic targets that may inform future treatment strategies. This review summarizes current findings on the immunological roles of renal epithelial cells in LN and discusses their relevance to the development of targeted and cell-specific therapeutic interventions.